Rise of the balloon goons - Cummings, Troy (Cummings, Troy. Notebook of doom, 2013)
Alexander has just moved into Stermont, but the elementary school is being torn down, his new classroom is located in the hospital morgue, a notebook he finds is full of information about monsters--and everywhere he turns there are spooky balloon men determined to attack him.